Global Mobile Satellite Communications For Maritime, Land and Aeronautical Applications - Ilcev, Stojce Dimov; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Global mobile satellite communications (GMSC) are specific satellite communication systems for maritime, land and aeronautical applications. It enables connections between moving objects such as ships, vehicles and aircrafts, and telecommunications subscribers through the medium of communications satellites, ground earth stations, PTT or other landline telecommunications providers. Mobile satellite communications and technology have been in use for over two decades. Its initial application is aimed at the maritime market for commercial and distress applications. In recent years, new developments and initiatives have resulted in land and aeronautical applications and the introduction of new satellite constellations in non-geostationary orbits such as Little and Big LEO configurations and hybrid satellite constellations as Ellipso Borealis and Concordia system. This book is important for modern shipping, truck, train and aeronautical societies because GMSC in the present millennium provides more effective business and trade, with emphasis on safety and commercial communications. Global Mobile Satellite Communications is written to make bridges between potential readers and current GMSC trends, mobile system concepts and network architecture using a simple mode of style with understandable technical information, characteristics, graphicons, illustrations and mathematics equations. Global Mobile Satellite Communications represents telecommunications technique and technology, which can be useful for all technical staff on vessels at sea and rivers, on all types of land vehicles, on planes, on off shore constructions and for everyone possessing satellite communications handset phones.
Space Segment -- Transmission Techniques -- Antenna Systems for Mobile Satellite Applications -- Propagation and Interference Consideration -- Inmarsat GEO GMSC System -- Cospas-Sarsat LEO and GEO GMSC Systems -- Non-GEO GMSC Systems -- Global Satellite Augmentation Systems (GSAS) -- Global Stratospheric Platform Systems (GSPS).
Keywords: Electrical engineering; Automotive engineering; Communications Engineering, Networks; Automotive Engineering; Electrical Engineering